Efficiency optimization of permanent magnet vernier for direct-drive application - Yeo, Jun Rong (Nanyang Technological University, 2024)
This paper addresses the challenge of high harmonic loss in direct-drive systems through a systematic design approach employing permanent magnet vernier motor (PMVM). The primary objective is to improve efficiency, performance standards, and minimize losses in various direct-drive applications such as electric vehicles and wind turbines. Key findings from the study include a comprehensive comparison of different design configurations, including uniform modular and tooth module design, uniform modular and yoke module design, hybrid modular and tooth module design and hybrid modular and yoke module design. All the designed models can reveal a notable reduction in losses compared to the original model. Particularly noteworthy is the yoke modular and hybrid modular design, which exhibits the least decline in torque and the highest percentage drop in both core losses and PM losses. However, it is emphasized that these findings are specific to the 18s56p PMVM, and further testing is required to draw conclusive judgments regarding design superiority.